2008
DOI: 10.1152/ajpendo.00562.2007
|View full text |Cite
|
Sign up to set email alerts
|

Postburn trauma insulin resistance and fat metabolism

Abstract: Cree MG, Wolfe RR. Postburn trauma insulin resistance and fat metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 119 publications
4
69
0
2
Order By: Relevance
“…Triglyceride stores develop in sites such as the liver and muscle cells, due to increased FFA delivery following catecholamine-induced lipolysis, decreased ß-oxidation within muscle, and decreased hepatic secretion of fats. These increases in intracellular triglyceride levels may contribute to the observed alterations in insulin signaling (40). In accordance with this, the IMCL accumulation detected by NMR in this study qualifies as a biomarker of altered insulin resistance and signaling in burn trauma.…”
Section: ------------------------------------------------------------supporting
confidence: 86%
“…Triglyceride stores develop in sites such as the liver and muscle cells, due to increased FFA delivery following catecholamine-induced lipolysis, decreased ß-oxidation within muscle, and decreased hepatic secretion of fats. These increases in intracellular triglyceride levels may contribute to the observed alterations in insulin signaling (40). In accordance with this, the IMCL accumulation detected by NMR in this study qualifies as a biomarker of altered insulin resistance and signaling in burn trauma.…”
Section: ------------------------------------------------------------supporting
confidence: 86%
“…Whereas the magnitude of reduction in pyruvate oxidation is in accord with our results, we found no reduction in the oxidation of other mitochondrial substrates, suggesting that more severe trauma is necessary for an overall impairment of mitochondrial oxidative capacity to develop. In support of this notion, burn injury is associated with more profound catabolism and markedly increased lipolysis, plasma FFA, and deposition of triglycerides in skeletal muscle (and liver) (2,12).…”
Section: E617mentioning
confidence: 89%
“…Studies that improved insulin sensitivity by low-calorie diets in patients with T2D were accompanied by a reduction in IMTG content (Jazet et al 2008, Lara-Castro et al 2008. Insulin resistance associated with ageing (Nakagawa et al 2007), growth hormone administration (Krag et al 2007) and post-burn trauma (Cree & Wolfe 2008) has been reported to be associated with increased IMTG content. Current opinion is reasonably clear on the fact that IMTG is a useful marker of the level of cytosolic lipid accumulation, but it is more likely that active lipid metabolites such as LCACoAs, DAGs and ceramides or intermediates of FA oxidation pathways interfere with insulin action via a variety of potential mechanisms (Fig.…”
Section: Linking Intramyocellular Triglyceride Content and Insulin Acmentioning
confidence: 99%